COMMUNICATING WITH THE MEDIA. PERSPECTIVES ON AN EMERGING DIGITAL NEWS INDUSTRY - NISTOR, Cristina (2016)
Over the last two decades media organizations and professionalcommunication have stepped into the fascinating,dynamic and stimulating realm of the Internet that haschallenged them to understand the new cyber‐geography,later to identify the new media consumers and, furthermore,to structurally redesign, again and again, news stories, mediastrategies and communication policies.In the new technological framework everybody can communicateand at the same time the availability and variety ofinformation has expanded so that the boundary between goodquality and poor quality information has become blurred(Krimsky, 2007).